2008
DOI: 10.1103/physrevb.78.045436
|View full text |Cite
|
Sign up to set email alerts
|

Stability, structure, and electronic properties of chemisorbed oxygen and thin surface oxides on Ir(111)

Abstract: We present ab initio calculations for atomic oxygen adsorption on Ir͑111͒ for a wide range of oxygen coverages, ⌰, namely from 0.11 to 2.0 monolayers ͑ML͒, including subsurface adsorption and thin surfaceoxide-like structures. For on-surface adsorption, oxygen prefers the fcc-hollow site for all coverages considered. Similarly to oxygen adsorption on other transition metal surfaces, as ⌰ increases from 0.25 ML to 1.0 ML, the binding energy decreases, indicating a repulsive interaction between the adsorbates. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 92 publications
13
47
0
Order By: Relevance
“…1(a) and are also given in Table I. In agreement with a previous computational study [41], we find on the clean Ir surface that the potential energy increases (corresponding to a decrease in stability) when the O coverage is increased from 0.25 to 0.50 ML. In the same study, the authors found also an increase in potential energy for coverages lower than 0.25 ML.…”
Section: A Coverage Dependencesupporting
confidence: 89%
“…1(a) and are also given in Table I. In agreement with a previous computational study [41], we find on the clean Ir surface that the potential energy increases (corresponding to a decrease in stability) when the O coverage is increased from 0.25 to 0.50 ML. In the same study, the authors found also an increase in potential energy for coverages lower than 0.25 ML.…”
Section: A Coverage Dependencesupporting
confidence: 89%
“…And E O/surf stands for the total energy of the oxygen adsorbate on the surface. This definition is the same with the one used in DFT calculation of binding energy for adsorbed oxygen on Ir(1 1 1) [15].…”
Section: Methodsmentioning
confidence: 95%
“…This binding energy value of O top is slightly higher than the binding energy value of 4.21 eV, which is a sum of the adsorption energy of oxygen atom 1.17 eV [4] for single O-Ir-O trilayer (6 Â 6) surface oxide on Ir(1 1 1)À(7 Â 7) and the binding energy of O 2 3.04 eV/O atom [15]. Hence, it is impractical to subtract two separate O top atoms and combine them in the gas phase.…”
Section: Energetics Of Surface Deoxygenationmentioning
confidence: 94%
“…Low energy electron diffraction (LEED) of the ordered ad-layer displays a diffraction pattern with a (2 × 2) periodicity. [23][24][25][26] Already early work interpreted the (2 × 2) LEED pattern to be the result of the superposition of three O-(2 × 1) superstructure domains consistent with a room temperature saturation coverage of 0.5 ML with respect to the Ir surface atom density. [23][24][25][26] Already early work interpreted the (2 × 2) LEED pattern to be the result of the superposition of three O-(2 × 1) superstructure domains consistent with a room temperature saturation coverage of 0.5 ML with respect to the Ir surface atom density.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Oxygen binds strongly to the Ir(111) substrate with an energy gain of more than 4 eV per oxygen adatom (referred to the energy of a free oxygen atom) [23][24][25][26] and, because it is saturated by its strong bond to Ir, binds only weakly to Gr. [32][33][34] Oxygen binds strongly to the Ir(111) substrate with an energy gain of more than 4 eV per oxygen adatom (referred to the energy of a free oxygen atom) [23][24][25][26] and, because it is saturated by its strong bond to Ir, binds only weakly to Gr.…”
Section: Introductionmentioning
confidence: 99%